Oral Microbiota Development in Early Childhood - Kennedy, Beatrice (Sci Rep, 2019)
Early life determinants of the oral microbiota have not been thoroughly elucidated. We studied the association of birth and early childhood characteristics with oral microbiota composition using 16 S ribosomal RNA (rRNA) gene sequencing in a population-based Swedish cohort of 59 children sampled at 6, 12 and 24 months of age. Repeated-measurement regression models adjusted for potential confounders confirmed and expanded previous knowledge about the profound shift of oral microbiota composition in early life. These alterations included increased alpha diversity, decreased beta diversity and alteration of bacterial composition with changes in relative abundance of 14 of the 20 most common operational taxonomic units (OTUs). We also found that birth characteristics, breastfeeding and antibiotic use were associated with overall phyla distribution and/or with the relative abundance of specific OTUs. Further, we detected a novel link between morning salivary cortisol level, a physiological marker of neuroendocrine activity and stress, and overall phyla distribution as well as with decreased abundance of the most common OTU mapped to the Streptococcaceae family. In conclusion, a major part of the maturation of the oral microbiome occurs during the first two years of life, and this development may be influenced by early life circumstances.